The effect of plyometric exercises in the development of vertical jumping and some types of shooting by jumping from different distances with basketball for students - Mohammed Ameen, Nada (International Journal of Psychosocial Rehabilitation, 2020)
Correction in the game of basketball is one of the most important offensive skills and the final result of all skills, and its goal is to score the largest number of points in the opposing team’s basket from anywhere and a distance on the field, and this requires two leg muscles that are distinguished by the strength of jumping. As for the importance of the research, it lies in the fact that the plyometric exercises enable the muscle to reach its maximum length in a short time, the moment of jumping to the top, which leads to the development of the vertical jump and then the correction on As for the research problem, it is that there is a weakness in the strength of the vertical jump for students during practical lessons When the correction is made from different distances, which confirms the lack of concentration of the material parameters by passing the plyometric. The research aims to prepare playground exercises for students and then identify their impact on the development of vertical jump, in addition to knowing their effect on developing some types of correction by jumping from different distances on the field. The researcher used the experimental method and the method of two equal experimental and control groups, and it was conducted on a random sample of the fourth stage in the method of (lottery) with a number of (16) sixteen students at a rate of 13.33%, then conducting the exploratory experiment and the previous and residual tests of the research variables, for example, on the combined experiment that lasted (8) Eight weeks, at a rate of two lessons per week, the research continued (03/11/2019 until 01/15/2020), in addition to the appropriate statistical methods. The researcher concluded that the effect of the Buliometric exercises in the vertical jump as well as in the development of some types of correction by jumping from different distances in addition to the emergence of the superiority of the experimental group and the control group in the research variables in the subsequent tests - dimensions. Free throw circuit, where the signal was not significant. The researcher recommends using the exercises that have been prepared and implemented in order to stabilize their dimensional and skillful effect, in addition to serious interest and focus on blindness exercises and diversifying them with practical lessons by allocating sufficient time to them.